Constructing addiction from experience and context: Peele and Brodsky's Love and Addiction revisited. - Kwee AW (Sexual Addiction & Compulsivity, 2007)
Peele and Brodsky (1975) first proposed the experiential-constructivist model of addiction utilizing the construct of compulsive interpersonal attachment (then not viewed as an addiction) as a vehicle to argue that substance addiction is rooted in experiential and contextual forces. One of these contextual forces is the prevalence of the disease mindset itself. With increasing legitimacy accorded to disordered love attachments as addiction 'diseases,' we can now explore this hypothesis in relation to sexual addiction using as illustration religious 'chaste sex addicts' and Homosexuals Anonymous. Treatment recommendations are then considered in the light of effective interventions outside of the disease model.